Rapid eye movement sleep without atonia may help diagnose Lewy body disease in middle‐aged and older patients with somatic symptom disorder. Issue 1 (12th January 2016) - Munechika, Takayuki; Fujishiro, Hiroshige; Okuda, Masato; Iwamoto, Kunihiro; Torii, Youta; Iritani, Shuji; Ozaki, Norio
Abstract: Background: Lewy body disease (LBD), including Parkinson's disease (PD) and dementia with Lewy bodies (DLB), is defined pathologically as degeneration in the central and peripheral nervous system associated with Lewy bodies. Somatic symptom disorder often predates the clinical diagnosis of PD and DLB. It is crucial to make an initial diagnosis of LBD in patients with psychiatric symptoms because administering psychotropic drugs often causes or exacerbates extrapyramidal signs. Given the close association between rapid eye movement (REM) sleep behaviour disorder and LBD, REM sleep without atonia on polysomnography may help to diagnose LBD in middle‐aged and older patients with somatic symptom disorder. Methods: We reviewed the clinical profiles of five patients with an initial diagnosis of somatic symptom disorder who exhibited REM sleep without atonia on polysomnography. There were three men and two women, with a mean age of 68.4 years (range: 55.0–78.0 years). The mean Mini‐Mental State Examination score was 26 (range: 22–30). Results: Only two patients had a clinical history of dream‐enacting behaviour and fulfilled the clinical criteria for REM sleep behaviour disorder, but clinical conditions in the other three patients corresponded to subclinical REM sleep behaviour disorder. Final clinical diagnoses were made as probable DLB in three patients; two patients did not meet the clinical criteria for PD or DLB. Neurological examinations revealed mild extrapyramidal signs in these two patients, and their scores on the motor component of the Unified Parkinson's Disease Rating Scale were 8 and 5 points, and their Mini‐Mental State Examination scores were 30 points. Neither patient exhibited dream‐enacting behaviour, but both had constipation. Cardiac 123 I‐metaiodobenzylguanidine scintigraphy revealed mild increased washout rates. Discussion: REM sleep without atonia may provide an opportunity to identify LBD in patients with somatic symptom disorder, even before they fulfil the clinical criteria for PD or DLB. Continued follow‐up will be needed to determine whether these psychiatric patients are in the prodromal stage of PD or DLB.